Acute Venous Congestive Myelopathy in a Patient with Neurosarcoidosis - Guy, Nicola Hazel (Journal of Neurological Surgery Reports, 2022)
There is a range of differential diagnoses for intramedullary lesions of the conus medullaris, both neoplastic and non-neoplastic. There is a limited role for surgery in a large proportion of these diagnoses, and operative risks can outweigh any benefits of surgery. Here a case is presented of a patient referred to a neurosurgical center for a biopsy of a presumed neoplastic conus tumor. However, through the collaboration of a multidisciplinary team, further diagnoses were considered. After thorough investigation, two conditions were diagnosed: venous congestive myelopathy secondary to inferior vena cava agenesis and spinal neurosarcoidosis. This case demonstrates the importance of neurosurgeons retaining a high degree of suspicion for alternative diagnosis to avoid unnecessary surgical risk.
Keywords: neurosarcoidosis; venous congestive myelopathy; cauda equina; intramedullary; myelopathy